Incorporation of waste plastic in asphalt binders to improve their performance in the pavement - Costa, Liliana M. B. (2013)
With the increase in road traffic more demands are placed on pavements, and thus the structural and functional performance of road pavements needs to be improved. One method that can greatly improve the quality of the flexible pavements is the addition of polymers to the bitumen or to the asphalt mixtures. Although the modification of bitumen with virgin polymers can improve the properties of asphalt mixtures, the use of recycled plastic may also show a similar result with additional environmental advantages. This work aims to evaluate the possible advantages of modifying the bitumen with different plastic wastes, namely polyethylene (high density HDPE and low density LDPE), ethylene-vinyl acetate (EVA), acrylonitrile–butadiene-styrene (ABS) and crumb rubber, in order to improve the properties of the resulting binders for use in high performance asphalt mixtures. The performance of modified binders with recycled polymers was compared with that of the conventional bitumen and the one of a commercial modified binder (Styrelf). The results of the laboratory tests (basic characterization, dynamic viscosity, resilience and storage stability) will be used in the selection of the best plastic waste materials and production conditions that should be used in the modification of bitumen in order to optimize its behaviour, emphasizing that this study aims to promote the reuse of plastic waste in a more environmental and economic way.